APPLICATION OF DRIBBLING VARIATIONS BASED ON PLAYING APPROACH TO IMPROVE STUDENT LEARNING OUTCOMES OF SMPN 2 SECANGGANG T.A. 2019/2020 - Ariansyah Panggabean; Agung Sunarno; Ardi Nusri (Indonesia Sport Journal, 2020)
This study aims to determine the improvement of dribbling learning outcomes through variations based on the play approach in class IX students of SMP Negeri 2 Secanggang T.A. 2019/2020. The subject of this research was carried out at SMP Negeri 2 Secanggang T.A. 2019/2020, the sample in this study was class IX-4 students, totaling 30 people. The research method used is the Classroom Action Research method. Based on the results of the initial tests conducted on students in class IX-4 of SMP Negeri 2 Secanggang, out of 30 students, only 6 students (20%) achieved a mastery level of learning with an average score of 55.8. The results of the first cycle of students there were 15 students (50%) who reached the level of mastery learning with an average value of 68.6. In the second cycle, there were 25 students (83.3%) who achieved the mastery level of learning with an average score of 80.7. This study concludes that through variations based on the play approach, it can improve the learning outcomes of dribbling in soccer games for grade IX-4 students of SMP Negeri 2 Secanggang T.A. 2019/2020.Keywords: Dribbling, Learning Results Dribbling, Approach to Play